PENERAPAN METODE 5S+SAFETY DI BAGIAN PRODUKSI PABRIK GULA - Dewi, Alifa Permata; Rachmadewi, Ira Promasanti; Qurtubi; Iryani, Devina Inayah (Metode : Jurnal Teknik Industri, 2024)
PT. PQR is a sugar factory company whose facilities are distributed unevenly throughout the factory, making the workers in the production division not very clean and organized. The research aims to identify problems in the work environment and provide suggestions regarding the issues found. Therefore, a method is needed to determine the work environment, namely 5S+Safety, using tools like a 6S assessment form for each aspect. The results obtained were 2.808, which means that the activities needed to be carried out more, and only a tiny part of the 6S was carried out. For short, with a value of 1.75; for set in order, with a value of 2.4; for shine, with a value of 2.8; for standardize, with a value of 3.2; for sustain, with a value of 3.4; and finally safety, with a value of 3. This research was used to determine the cultural conditions and work environment that can be used as evaluation material for this company to create a clean, comfortable, and safe work environment.